2004
DOI: 10.1097/01.ju.0000125200.13430.8a
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With Clean Intermittent Catheterization in Children With Spina Bifida

Abstract: The incidence of genitourinary complications associated with CIC in children with spina bifida is low. We identified 2 complications during a period of 570 patient-years for an incidence of 3.5 complications/1000 patient-years (95% confidence interval -1.3, 8.3) of observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 16 publications
1
14
0
5
Order By: Relevance
“…Prostatitis, epididymo-orchitis and urethritis are less frequent complications; occasional urethral trauma has also been reported. 25,26 Concerns about urethral strictures and false passage have been raised but the incidence appears to be similar between those using IC and those who are not.…”
Section: Catheterizationmentioning
confidence: 83%
“…Prostatitis, epididymo-orchitis and urethritis are less frequent complications; occasional urethral trauma has also been reported. 25,26 Concerns about urethral strictures and false passage have been raised but the incidence appears to be similar between those using IC and those who are not.…”
Section: Catheterizationmentioning
confidence: 83%
“…Campbell et al reported that 45 Canadian children learned to perform ISC at a mean age of 8 years (range 4.7-15.3 years) [22]. In this US cohort, the mean age to ISC was 9.45 years (SD = 2.97 years; range 2 to 17 years) and in those individuals with known intellectual disability, it was 12.2 years (SD = 2.96 years).…”
Section: Discussionmentioning
confidence: 95%
“…Especially during the early rehabilitation phase, when patients are instructed on how to perform intermittent catheterization acute urethral false passages are possible. 2 Urethral strictures seem to be related to previous urethral lesions. Günther et al 1 demonstrated that a history of indwelling catheters or urethral lesions is correlated with a higher incidence of urethral strictures in men performing intermittent catheterization.…”
Section: Discussionmentioning
confidence: 99%